MEMBANGUN KESADARAN ANTI-BULLYING DI LINGKUNGAN SD: PROGRAM PENGABDIAN MAHASISWA KKN - Hikmah Anisatul Mutmainah; Syahadat Sadwina Iskandar; Deni Sapto Wibowo; Alif Rizki Baihaqi; Mutiara Sari (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
Bullying in elementary schools remains a critical issue that negatively affects students’ psychological well-being, academic achievement, and the overall learning climate. The Indonesian Ministry of Education, Culture, Research, and Technology (Permendikbudristek) Regulation No. 46 of 2023 on the Prevention and Handling of Violence in Educational Institutions (PPKSP) mandates a systematic response to prevent and address school violence, including bullying. This article describes a community service program in the form of an anti-bullying socialization activity conducted by students of the Community Service Program (KKN) from Universitas Muhammadiyah Lampung (UML) at SDN 1 Wates, Pringsewu, on July 31, 2025. The activity was part of the broader KKN program held from July 28 to August 20, 2025, targeting students from grades 1 to 6. The program’s method combined outdoor sessions for all classes, interactive question-and-answer activities, and in-class reinforcement for grades 5 and 6 through case discussions and collective commitments. The materials emphasized the definition of bullying, its forms, impacts, and safe prevention and reporting strategies. The results revealed high enthusiasm among students, improved understanding of bullying, and an initial commitment from the school to follow up with simple reporting mechanisms and improved school rules. This program is aligned with the UNESCO-recommended whole-school approach and strengthens child-friendly school ecosystems in rural communities. With digital literacy integration, teacher–parent involvement, and institutional follow-up, such initiatives have the potential to serve as a model for developing safe schools through community-based engagement.